Carbon Nanotubes for Photovoltaics: From Lab to Industry. Issue 3 (12th November 2020) - Wieland, Laura; Li, Han; Rust, Christian; Chen, Jianhui; Flavel, Benjamin S.
Abstract: The use of carbon nanotubes (CNTs) in photovoltaics could have significant ramifications on the commercial solar cell market. Three interrelated research directions within the field are crucial to the ultimate success of this endeavor; 1) separation, purification, and enrichment of CNTs followed by 2) their integration into organic solar cells as a photosensitive element or 3) in silicon solar cells as a hole selective contact. All three subtopics have experienced tremendous growth over the past 20 years and certainly the performance of the silicon‐based cells is now rapidly approaching that of those on industrial production lines. With a view to these three research areas, the purpose of this Progress Report is to provide a brief overview of each field but more importantly to discuss the challenges and future directions that will allow CNT photovoltaics to move out of the research lab and into end user technology. These include efforts to upscale CNT purification, improvements in power conversion efficiency, increased light absorption, the identification of new material combinations, passivation strategies, and a better understanding of charge separation and energy transfer within these systems. Abstract : The potential for carbon nanotubes in the field of photovoltaics is multifaceted and broad. This Progress Report examines their use in organic and silicon based solar cells and discusses the challenges related to future industrial application.